‘Would It Take Four?’: Reading Jared Carter’s ‘Ethel’ Through New Criticism Lens - Betharia Noor Indah Sari; Nur Wulan; Syahrur Marta Dwi Susilo; Ida Nurul Chasanah (Interference: Journal of Language, Literature, and Linguistics, 2026)
Abstract. This paper presents a systematic close reading of Jared Carter’s poem ‘Ethel’ through the lens of New Criticism. New Criticism is a literary theory that treats a text as a self-contained object of knowledge. The poem ‘Ethel’ depicts the 1953 execution of Ethel Rosenberg by electric chair. However, in this study, the poem ‘Ethel’ is independent of historical or biological context, author’s intention, or reader’s response. This study employs a qualitative textual analysis methodology, utilizing a five-step systematic close reading instrument: (1)visual mapping of line breaks and indentation; (2)reconstruction of syntax baseline; (3)cataloguing deviations from the baseline; (4)categorization of diction by semantic field and register, and (5)analysis of grammatical voice. Through this methodology, the study reveals the findings of Carter’s use of enjambment, caesura, and indentation creates a ‘structure of interruption’ that mirrors the electrical interruptions in the poem’s content. The analysis identifies a paradox, where bureaucratic terminology (stethoscopes, warden, signaled) collides with imageries (plume, smoke, rose). The grammatical passive voice showcases structural irony, where active verbs are empty (They), inanimate actor (stethoscopes), or modal (had seemed). Meanwhile, the only unqualified active verb (rose) is granted to smoke, rather than to human. These all together generate organic unity. The poem does not create meaning through what it explicitly states about Ethel Rosenberg’s execution. The poem achieves its meaning through how its formal features enact limits of witness, memory, and knowledge. These findings carry global implications for literary pedagogy and critical methodology. They demonstrate that New Criticism’s systematic close reading remains a replicable, teachable, and verifiable model for textual analysis across diverse educational contexts. New Criticism offers a transferable framework that enables readers worldwide to analyze poetry through its internal structural relationships rather than external contexts. The study contributes to formalist methodology in an era of computational text analysis. It asserts that human-centered close reading provides irreplaceable interpretive depth that computation approaches cannot replicate. Keywords: New Criticism, close reading, poetry, Jared Carter, Ethel Rosenberg